2017
DOI: 10.1158/1535-7163.mct-17-0040
|View full text |Cite
|
Sign up to set email alerts
|

CDK4/6 Inhibitors Sensitize Rb-positive Sarcoma Cells to Wee1 Kinase Inhibition through Reversible Cell-Cycle Arrest

Abstract: Research into the biology of soft tissue sarcomas has uncovered very few effective treatment strategies that improve upon the current standard of care which usually involves surgery, radiation, and chemotherapy. Many patients with large (>5cm), high-grade sarcomas develop recurrence, and at that point have limited treatment options available. One challenge is the heterogeneity of genetic drivers of sarcomas, and many of these are not validated targets. Even when such genes are tractable targets, the rarity of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 51 publications
5
32
0
Order By: Relevance
“…For example, CDK4/6 inhibitors cooperate with PI3K inhibitors in breast cancer models [46] and sensitize pancreatic cancer cell lines to MEK and mTOR inhibitors [34,47]. Another study showed that RB-proficient sarcoma cells were sensitized to Wee1 kinase inhibition after prior transient treatment with PCB [48]. This novel sequential combination treatment exploited the reversibility of PCB to synchronize the cells thus maximizing the effects of the kinase inhibitor during the ensuing S and G2 phases.…”
Section: Discussionmentioning
confidence: 99%
“…For example, CDK4/6 inhibitors cooperate with PI3K inhibitors in breast cancer models [46] and sensitize pancreatic cancer cell lines to MEK and mTOR inhibitors [34,47]. Another study showed that RB-proficient sarcoma cells were sensitized to Wee1 kinase inhibition after prior transient treatment with PCB [48]. This novel sequential combination treatment exploited the reversibility of PCB to synchronize the cells thus maximizing the effects of the kinase inhibitor during the ensuing S and G2 phases.…”
Section: Discussionmentioning
confidence: 99%
“…For example, palbociclib treatment of melanoma cells for more than 3 days led to the induction of senescence in association with a decreased sensitivity to vemurafenib (Yoshida et al 2016). Likewise, Rb-expressing sarcoma cell lines with reversible palbociclib-induced cell cycle arrest were sensitive to co-treatment with the WEE1 kinase inhibitor AZD1775 (Francis et al 2017). Unfortunately, CDK4/6 inhibitor-induced senescence may also result in an undesirable outcome in the stroma through the promotion of a proinflammatory, senescence-associated secretory phenotype (SASP).…”
Section: Short-term Adaptation To Cdk4/6 Inhibitorsmentioning
confidence: 99%
“…Many of the studies demonstrated that monotherapy targeting specific CDKs induces a reversible cell cycle arrest, as expected. Some studies, however, revealed additional benefits of CDK inhibition including downregulation of other CDKs [200,201], decreased migration [141,202], and enhanced efficacy of other targeted agents [203,204]. Among the rationale combination therapies evaluated, THZ531, a CDK12 inhibitor, was found to synergize with PARP inhibitors to prevent DNA damage repair and induce tumor cell death in EwS, significantly diminishing the tumor growth in mouse xenograft and PDX models of the disease [205].…”
Section: Cdk-targeted Anti-cancer Therapymentioning
confidence: 99%